PERKAWINAN CAMPUR ANTARA ETNIS BATAK-DAYAK DI KALIMANTAN BARAT - Lyudmita Karolina M. Bakara; Efriani Efriani; Susiana Susiana; Meliya Fransiska; Oktaviana Supriani Ririn (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2020)
Intermarriage is a familiar phenomenon in Indonesia, mainly because of various cultures, religions, and ethnicities.The phenomenon of intermarriage also occurs between the Batak ethnic and Dayak ethnic groups in West Kalimantan.The cultures of these two ethnicities are very different. Thus, this study proposes to examine the pattern of decision making in determining marital customs and also determine the kinship system passed on to offspring those born from intermarriage these two ethnicities. The study was conducted with qualitative methods which were carried out descriptively. Data, which consists of information about the kinship system, the culture used in marriage, and also the kinship system that is passed on to offspring, was collected by interview and observation. From the data obtained, the culture of the Batak ethnic kinship system is very different from the Dayak ethnicity, so the marriage customs and the descendant system are also very different. Families who engage in mixed marriages, carry out a marriage process using one culture and be found those who use both cultures take turns. Forwarding the kinship system to offspring is generally dominated by the Batak ethnic kinship system.